2003
DOI: 10.2337/diacare.26.10.2848
|View full text |Cite
|
Sign up to set email alerts
|

Nonremovable, Windowed, Fiberglass Cast Boot in the Treatment of Diabetic Plantar Ulcers

Abstract: A nonremovable fiberglass cast boot was effective in healing diabetic plantar ulcers and in decreasing the risk of secondary osteomyelitis. The cast boot forced compliance with off-loading, thus promoting healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 16 publications
1
59
0
2
Order By: Relevance
“…The percentages of healed ulcers in 12 weeks are comparable to percentages previously found for removable knee‐high prefabricated walkers, 52–79% , and for half shoes or other healing shoes, 43–70% . Time to healing in the cast shoe and FOS was comparable to what was found in previous studies testing similar type (cast) shoes: 60–70 days on average .…”
Section: Discussionsupporting
confidence: 82%
“…The percentages of healed ulcers in 12 weeks are comparable to percentages previously found for removable knee‐high prefabricated walkers, 52–79% , and for half shoes or other healing shoes, 43–70% . Time to healing in the cast shoe and FOS was comparable to what was found in previous studies testing similar type (cast) shoes: 60–70 days on average .…”
Section: Discussionsupporting
confidence: 82%
“…In the study of Ha Van et al (25), the presence of a persistent ulcer prompted clinicians to provide patients with a TCC rather than an orthopedic cast walker boot, and patients treated with a TCC achieved better outcomes. It could be hypothesized that the “persistent ulcer” in the study of Ha Van et al might have played a role similar to that of the “previous ulcer” in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane systematic review and meta‐analysis included five randomized controlled trials (RCTs) with a cumulative total of 230 patients and found a relative risk ratio of 1.17 [95% confidence interval (CI) 1.01–1.36, p = 0.04] for non‐removable offloading to achieve healing compared with removable offloading . Another systematic review and meta‐analysis included ten randomized and non‐randomized clinical studies with a cumulative total of 524 patients and showed a significantly higher relative risk ratio of 1.43 (95% CI 1.11–1.84, p = 0.001) for non‐removable offloading to achieve healing compared with removable offloading . Based on two relatively small RCTs , there is evidence to suggest that a removable walker rendered irremovable is as effective as a TCC in healing neuropathic plantar forefoot ulcers (Relative risk ratio = 1.06; 95% CI 0.88–1.27, p = 0.31) .…”
Section: Casting and Prefabricated Healing Devicesmentioning
confidence: 99%